Thyroid Pathology in High-Risk Cardiac Surgery Patients with Coronary Artery Disease - Gogayeva, Olena K.; Rudenko, Anatoliy V.; Lazoryshynets, Vasyl V.; Rudenko, Serhii A.; Andrushchenko, Tetiana A. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To analyze the features of the perioperative period in high-risk cardiac surgery patients with coronary artery disease (CAD) and thyroid disease. Materials and methods. Retrospective analysis of data of 354 high-risk patients with CAD who were operated and discharged from the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine from 2009 to 2019. All the patients underwent standard clinical and laboratory tests, ECG, echocardiography, coronary angiography and surgical myocardial revascularization with correction of concomitant cardiac pathology. Ultrasound screening of thyroid disease and thyroid hormone levels was not performed in all patients, however, patients with severe symptoms were referred for follow-up. Results. Thyroid disease was diagnosed in 37 (10.4%) patients, of whom 11 (3.1%) had hypothyroidism and were receiving hormone replacement therapy, and 1 (0.28%) had hyperthyroidism on tyrosol therapy. Ultrasound signs of thyroiditis were detected in 7 (1.9%) patients, nodular goiter in 29 (8.1%), and retrosternal goiter in 1 (0.28%) patient. Depending on the cardiac surgical pathology, the prevalence of hypothyroidism did not differ in patients with uncomplicated and complicated forms of CAD (7 [3.6%] and 4 [2.5%] patients, respectively, p = 0.5498). Patients with hypothyroidism received hormone replacement therapy with levothyroxine in a dosage prescribed by an endocrinologist. The day before the surgery, thyroid-stimulating hormone control was performed to confirm the achievement of compensation. When comparing the course of the operative period in compensated hypothyroidism and clinical euthyroidism, no significant differences were found, and the postoperative period didn’t differ in the occurrence of atrial fibrillation (p = 0.0801), hydrothorax (p = 0.5280), but a decrease in the estimated glomerular filtration rate at discharge was found in patients with hypothyroidism (59.5 ± 16.8 vs. 71.3 ± 19.6 ml/min/1.73 m2, p = 0.0493). Conclusions. Timely detection of thyroid dysfunction allows to compensate the condition and avoid postoperative complications. Analysis of the perioperative period in patients with hypothyroidism showed no effect of compensated hypothyroidism on the operative and postoperative periods in high-risk patients with CAD. Decreased glomerular filtration rate after surgery in patients with hypothyroidism requires further study and adherence to the strategy of nephroprotection in polymorbid patients.